2021
DOI: 10.1007/s11136-021-02857-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and occupational performance of children with cancer in the era of the COVID-19 pandemic in terms of rehabilitation

Abstract: Purpose This study was designed to determine the changes in the quality of life (QOL) and occupational performance of children with cancer and to examine their rehabilitation needs during the pandemic period in Turkey. Methods 60 children with cancer and their families participated in the study. The first and second assessments were carried out in April and September 2020, respectively. The pediatric quality of life inventory parent proxy-report was used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
1
11
1
1
Order By: Relevance
“…However, people with chronic diseases have a lower psychological status due to their many physical problems (25). Distance from community and friends, closure of health centers, high rumors about the virus, high transmission power, lack of definitive treatment, and stress caused by the disease caused patients with chronic diseases to have many mental and physical problems during these two years (19). Meanwhile, patients with cancer are at higher risk for COVID-19 because they have a weaker immune system (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, people with chronic diseases have a lower psychological status due to their many physical problems (25). Distance from community and friends, closure of health centers, high rumors about the virus, high transmission power, lack of definitive treatment, and stress caused by the disease caused patients with chronic diseases to have many mental and physical problems during these two years (19). Meanwhile, patients with cancer are at higher risk for COVID-19 because they have a weaker immune system (33).…”
Section: Discussionmentioning
confidence: 99%
“…Before the epidemic, patients had the experience of not being understood by their friends and family due to sensitivity to health and were labeled obsessive, but now they feel normal and are confirmed by others regarding the correctness of the observance of health standards. Patients who were recovering reported that the epidemic gave them a valuable perspective (19). The lack of organized psychological services was one of the reasons for the decline in QoL and mental health of cancer patients during the COVID-19 pandemic in addition to patients' psychological turmoil (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Productivity. Ten articles (Anakwe et al, 2021;Brown & Lynch, 2022;Gadermann et al, 2022;Güney et al, 2022;Kara et al, 2021;Kirsch et al, 2021;Krishnaratne et al, 2022;Park et al, 2022;Tulchin-Francis et al, 2021;Önal et al, 2021) regarded the changes in occupations related to the productivity, especially education, of children during the COVID-19 pandemic. In order to contain the COVID-19 pandemic, several measures had to be taken by governments worldwide, including remote education, reduced attendance in school classes, testing, use of masks, thorough cleaning and handwashing, ventilation etc.…”
Section: Changes In Occupational Engagement and Behavioursmentioning
confidence: 99%
“…Меры, принятые почти во всех странах для борьбы с пандемией, ввергают весь мир в масштабный кризис и, как следствие, в глубокую глобальную рецессию. ECONOMIC SCIENCES (08.00.05, 08.00.10, 08.00.13, 08.00.14) В настоящее время активно исследуются вопросы влияния пандемии на психологическое и физическое состояние человека [1,2], качество его жизни и обеспечение населения медицинскими услугами, а также анализируются экономические и демографические последствия [3][4][5].…”
unclassified